2017
DOI: 10.3390/polym9050165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maleic Anhydride-Modified Poly(lactic acid) on the Properties of Its Hybrid Fiber Biocomposites

Abstract: This work investigated the effect of maleic anhydride (MA)-modified poly(lactic acid) (PLA), which is melt-blended with different untreated and aqueous borax (BR)-treated hybrid oil palm empty fruit bunch fibers (EFBF)/Kenaf core fibers (KCF), and compression-molded into corresponding hybrid biocomposites. These hybrid systems includes BR-treated EFBF/BR-treated KCF reinforced MA-modified PLA i.e., BR(EFBF-KCF)-MAPLA, BR-treated EFBF/BR-treated KCF reinforced unmodified PLA i.e., BR(EFBF-KCF)-PLA, untreated EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 49 publications
2
44
0
Order By: Relevance
“…Materials 2019, 12, x FOR PEER REVIEW 11 of 21 g-MAH was confirmed by the two C-H stretching peaks at 2914 cm −1 and 2847 cm −1 , along with the MAH peak at 1715 cm −1 [41]. ABS was identified by acrylonitrile at 2237 cm −1 , C=C stretching vibrations at 1637 cm −1 , and styrene aromatic ring stretching vibrations at 1494 cm −1 .…”
Section: Effects Of Blending Printing and Thermal Agingmentioning
confidence: 91%
See 1 more Smart Citation
“…Materials 2019, 12, x FOR PEER REVIEW 11 of 21 g-MAH was confirmed by the two C-H stretching peaks at 2914 cm −1 and 2847 cm −1 , along with the MAH peak at 1715 cm −1 [41]. ABS was identified by acrylonitrile at 2237 cm −1 , C=C stretching vibrations at 1637 cm −1 , and styrene aromatic ring stretching vibrations at 1494 cm −1 .…”
Section: Effects Of Blending Printing and Thermal Agingmentioning
confidence: 91%
“…The merging of the associated group (CH 3 ) of PP into the ABS blend shows the synergy [43] between the saturated hydrocarbons of three polymers. The absence of the MAH peak at 1715 cm −1 for the PE-g-MAH in blend pellets was also a sign of the chemical interactions [41] between the three polymers. Furthermore, it can be analyzed in Table 5 that, apart from the butadiene group at 1637 cm −1 , all remaining groups showed high intensity as compared to the neat ABS with no shift or minimum shift.…”
Section: Effects Of Blending Printing and Thermal Agingmentioning
confidence: 98%
“…To improve the interfacial adhesion between natural fibers and PLA, modifications of natural fiber and PLA, separately or simultaneously, have been undertaken before raw material compounding [1,6,[10][11][12]. PLA has been autoclaved to obtain different molecular weights of PLA, and its hydrophilicity was improved to result in a good mixability with hydrophilic materials, such as carbon nanotubes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A silane coupling agent (such as KH550) has been commonly applied in the composite to improve the interfacial adhesion between fibers and the polymer through an ester-exchange reaction between the silane and hydroxyl groups of the fibers; additionally, the mechanical properties of composites have been found to be enhanced, and the serving life of composites has been found to be extended [1,22]. The performances of composite with maleated and a silane-modified natural fiber have been extensively studied, and the effect of modifier content on the properties of composites has also been investigated in previous studies [12,[21][22][23][24][25]. However, few studies have been reported to compare the properties of natural fiber-reinforced composites between different chemical modifications of natural fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical, thermo-mechanical or chemo-thermo-mechanical treatments have been used to modify the chemical composition of the fiber surfaces, reducing the presence of lignin and extractives and increasing the presence of cellulose and hemicelluloses [12][13][14][15]. Furthermore, the use of maleic anhydride-grafted polyolefin as a coupling agent has provided a solution to obtain strong interphases [16][17][18][19]. However, the percentage of coupling agent against reinforcement content impacts the strength of the interphase and must be precisely dosed [18].…”
Section: Introductionmentioning
confidence: 99%